Isolation of Coumarins and Coumarin Glucoside from Launaea resedifolia - Gherraf, Noureddine; A. El-Bassuony, Ashraf; Zellagui, Ammar; Rhouati, Salah; A. Ahmed, Ahmed; Ridha Ouahrani, Mohammed (Asian Journal of Chemistry, 2010)
From the aerial parts of Launaea resedifolia, four coumarin compounds were isolated: cichoriin I, esculetin II, scopoletin III and isoscopoletin IV.